Rh(III)-Catalyzed Imidoyl C–H Carbamylation and Cyclization to Bicyclic [1,3,5]Triazinones - Confair, Danielle N. (Org Lett, 2020)
A Rh(III)-catalyzed synthesis of bicyclic [1,3,5]triazinones from a diverse array of imines coupled with ethyl (pivaloyloxy)carbamate is reported. The preparation of [5,6]- and [6,6]-bicyclic heterocycles substituted with aryl, alkyl and alkoxy groups demonstrated a broad reaction scope. The efficiency of this approach was further enhanced with the development of a three-component variant featuring in situ imine formation. X-ray crystallographic characterization of a rhodacycle formed by imidoyl C-H activation provides support for the proposed mechanism.